Towards a sustainability management tool for food manufacturing small and medium-sized enterprises—Insights from a Delphi study - Rebekka Küchler; Birte Maja Nicolai; Christian Herzig (Corporate Social Responsibility and Environmental Management, 2022)
Small and medium-sized enterprises (SMEs) are crucial for a sustainable development of the food sector. Common tools to manage and improve business sustainability are not applied widely amongst food manufacturing SMEs yet. Therefore, this paper derives important aspects to consider for an SME-suitable tool, based on an extract from a Delphi study. By conducting qualitative analysis of expert opinions, light is shed on needed initial requirements of a sustainability management tool for SMEs to use it. Furthermore, important conditions to create credibility are elaborated on, which can increase the application value of a sustainability management tool for SMEs. The different aspects hint at a sustainability management tool integrating not only sustainability assessment but also reporting and certification. With regard to content, the present paper recommends application of sustainability management tools for food manufacturing SMEs that take a holistic view on sustainability, including not solely the environmental but also social, economic and governance dimensions. The aspects explored through the present research lay a foundation for the development of a sustainability management tool for food manufacturing SMEs and can assist practitioners and researchers.
Keywords: 650; business sustainability; Delphi study; food manufacturing; SME; sustainability management; sustainable development